Hubungan Pengetahuan Level Undercoat Dengan Kemampuan Teoritis Pewarnaan Rambut Double Application Pada Mahasiswi Tata Rias Angkatan 2022 UNESA - Nonik Silvi; Octaverina Kecvara; Mutimmatul Faidah; Dindy Sinta Megasari (Program Studi Pendidikan Tata Rias, 2025)
In the academic environment of the Cosmetology Study Program at UNESA, female students are expected to not only understand the concept of hair coloring but also be able to understand the theoretical concepts in applying hair coloring techniques accurately. This study aims to identify the level of knowledge of female students regarding undercoat levels, assess their ability to perform double application hair coloring, and analyze the relationship between the two variables. This study employs a quantitative correlational approach involving female students from the Hair Styling Program at UNESA, class of 2022. The research instruments consist of a knowledge test, and data analysis was conducted using Pearson's correlation test. The results show that the average score for undercoat knowledge is 88.6, and the score for double application coloring ability is 84.8—both categorized as very good. The data were normally distributed, and the correlation analysis showed a coefficient of 0.997 with a p-value of 0.001, indicating a very strong and statistically significant relationship between undercoat knowledge and theoretical ability in double application hair coloring. Based on these findings, it is recommended that theoretical concepts at the undercoat level be further strengthened through a more contextual learning approach. Students are encouraged to further develop their foundational knowledge to support practical skills. Future research is recommended to incorporate direct practical elements to achieve more comprehensive results. Keywords: undercoat, hair coloring, double application, knowledge, make-up